Design, Synthesis and Potential Anti-Proliferative Activity of Some Novel 4-Aminoquinoline Derivatives - Ghorab Mostafa M.; Al-Said Mansour S.; Arafa Reem K. (Acta Pharmaceutica)
Novel nineteen compounds based on a 4-aminoquinoline scaffold were designed and synthesized as potential antiproliferative agents. The new compounds were N-substituted at the 4-position by aryl or heteroaryl (1-9), quinolin- 3-yl (10), 2-methylquinolin-3-yl (11), thiazol-2-yl (12), and dapsone moieties (13, 14 and 18). Bis-compounds 15, 16 and 19 were also synthesized to assess their biological activity. All the newly synthesized comounds were tested for in vitro antiproliferative activity against the MCF-7 breast cancer cell line. Seventeen of the novel compounds showed higher activity than the reference drug doxorubicin. The corresponding 7-(trifluoromethyl)-N-(3,4,5-trimethoxyphenyl)quinolin-4- amine 1, N-(7-(trifluoromethyl)quinolin-4-yl)quinolin- 3- amine (10), 2-methyl-N-(7-trifluorome-thyl)quinolin-4-yl) quinolin-3-amine (11) and N-(4-(4-aminophenylsulfonyl) phenyl)-7-chloroquinolin-4-amine (13) were almost twice to thrice as potent as doxorubicin. Biological screening of the tested compounds could offer an encouraging framework in this field that may lead to the discovery of potent anticancer agents.